Review of the African genus Digentia Stål, 1878 (Orthoptera, Acrididae, Oxyinae) - Charly Oumarou Ngoute; C. H. F. Rowell (Journal of Orthoptera Research)
The genus Digentia Stål, 1878 currently has four described species from the tropical forest areas of West Central Africa. Here, we describe a new species, Digentia viridissima sp. nov., and its natural habitat in the swamps of the humid forests of southern Cameroon. Additionally, we include a description of Digentia punctatissima (Stål, 1875) and redescriptions of Digentia rufogeniculata (Bolívar, 1911), Digentia fasciata Ramme 1929, and Digentia karnyi Ramme 1929. We also provide a key to identify the species of the genus.